0PERAN ICRC DALAM MENGINISIASI PENGAWASAN AUTONOMOUS WEAPON SYSTEM PADA KEPATUHAN HUKUM HUMANITER INTERNASIONAL - Febriyan, Muhammad Alvin; Hadi, Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research explains the role of the ICRC in initiating surveillance of autonomous weapon systems on international humanitarian law compliance. The role of the International Committee of the Red Cross (ICRC) in initiating surveillance of Autonomous Weapon Systems (AWS) is crucial to ensure compliance with International Humanitarian Law (ILH). This research uses a qualitative method with data collection techniques through literature studies sourced from several books, journals, documents, and websites. This research uses the theory of Positivism and has a research focus on the ICRC's initiation of AWS supervision in 2020 to 2023. The study showed the ICRC emphasizes that autonomous weapon systems must be designed and used taking into account the principles of IHL, including the distinction between combatants and non-combatants and proportionality in the use of force. In addition, the ICRC called for the need for effective human oversight in any use-of-force decisions by AWS, to maintain accountability and prevent lawlessness. The results show that despite progress in international discussions on AWS, there is still a need for a stronger legal framework to ensure compliance with IHL and prevent potential misuse of this technology in the future. Keywords: ICRC, AWS, International Humanitarian Law